2018
DOI: 10.1002/zamm.201800179
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation barriers for the cubic‐to‐tetragonal phase transformation in the absence of self‐accommodation

Abstract: The austenite‐to‐martensite phase transformation is characterized by the creation and growth of small nuclei of the new martensitic phase. Within a geometrically linear description and including an interfacial energy, we show that the minimal energy scales like V1113 in the volume V of the nucleus for V≫1 when primarily only two martensite variants are present. This complements the findings in [Knüpfer, Kohn, Otto, CPAM 2012] where it has been shown that the minimal energy of the transient nuclei has the lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Our result should be viewed in the context of scaling laws in the calculus of variations in general and more specifically in the modelling of shape-memory alloys and related phase transformation problems (see [37] and [45] for surveys on this). In the context of the modelling of shape-memory alloys, scaling laws, providing some insights on the possible behaviour of energy minimizers, have been deduced in various settings [3,5,6,8,9,14,15,20,[34][35][36][38][39][40][41][42]55]. For certain models, in subsequent steps, even finer properties (such as for instance almost periodicity results) have been derived [13].…”
Section: Relation To the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Our result should be viewed in the context of scaling laws in the calculus of variations in general and more specifically in the modelling of shape-memory alloys and related phase transformation problems (see [37] and [45] for surveys on this). In the context of the modelling of shape-memory alloys, scaling laws, providing some insights on the possible behaviour of energy minimizers, have been deduced in various settings [3,5,6,8,9,14,15,20,[34][35][36][38][39][40][41][42]55]. For certain models, in subsequent steps, even finer properties (such as for instance almost periodicity results) have been derived [13].…”
Section: Relation To the Literaturementioning
confidence: 99%
“…For (36) to hold for some m ∈ N a necessary condition is that α satisfies α| log( )| > log(Md). Under this assumption on α (which will be satisfied by our choice of α in terms of , see below), ( 36) is satisfied for m > 1 α − 2.…”
Section: Proof Of Proposition 3 Step 1: Choices Of Parameters In the Bootstrap Iterationmentioning
confidence: 99%
“…Nucleation and related problems in shape memory alloys have been e.g. considered in [43][44][45]. There are various other related models from materials science where dilute/large volume regimes are relevant, such as epitaxial growth (e.g.…”
Section: (C) Comparison To Previous Resultsmentioning
confidence: 99%
“…In their model one partial derivative is constrained to take only two values, leading to the characteristic non-convexity. Their work has been meanwhile generalized to different volume fractions [19,59], to vectorial settings in the context of linearized elasticity [3,10,11,23,36,38,39,49,52] and to geometrically nonlinear formulations [12,50]. These vectorial generalizations have confirmed that the Kohn-Müller scalar model indeed captures the correct scaling of the energy.…”
Section: Introductionmentioning
confidence: 89%